D4N2024 Presentation Showcase – Plenary Session: Aligning Actions Across Sectors to Achieve Healthy Diets and Nutrition Goals: Insights from Sri Lanka - Wijesinghe, Supun; Koyratty, Nadia; Marshall, Quinn; Rebello, Gerard (International Food Policy Research Institute, 2024)
Can behavioral change interventions improve nutrition at scale? Challenges and opportunities in Sri Lanka Supun Wijesinghe, Consultant, Health Promotion Bureau, Government of Sri Lanka